Angústia e sexualidade: A descoberta freudiana - Dal-Cól, Denise Maria Lopes [UNESP]; Palma, Claudia Maria de Sousa (My University, 2011)
Anxiety has a twofold importance in the psychoanalytic practice: the direction of treatment relies on this emotion for formulating a diagnosis as well as for the development of the treatment itself. Therefore, this paper aims at analyzing this concept and contributing to the metapsychological field, and by extension, to the clinical procedures. The discussion is a result of formulations elaborated in a master's dissertation that contemplated the following elements: clinical and theoretical facts that drew Freud's interest to anguish; the directions developed by Freudian trajectory and the established clinical repercussions.
Anxiety and sexuality: The Freudian discovery
Keywords: Anxiety; Psychoanalysis; Sexuality